HIGH-PERFORMANCE COMPUTING FOR SOLUTIONS OF CIRCULATING INCOMPRESSIBLE VISCOUS FLOWS IN A CAVITY - Sakypbekova, М.; Gusmanova, Ф.; Adylzhanova, С.; Toiganbayeva, Н.; Cherikbayeva, Л. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
With the rapid development of computer technologies, computational fluid dynamics (CFD) plays an important role in the analysis of aerodynamic characteristics, efficient design and study of complex flow mechanism. The problem of incompressible viscous fluid flow in a cavern is considered. This problem is widely used to evaluate CFD solvers, since the solution of the problem is known in detail depending on the Reynolds number, mesh size and required time steps, the solution of the problem requires significant computational resources. Based on this calculation, the optimum result was obtained on the GPU at Re numbers of 100, 400 and using different grid sizes. A comparative analysis of the performance of central and graphics processors has been carried out and it is shown that the program execution time on the graphics processor has increased significantly. The comparison of computation time shows the advantage of graphics processor technology in solving engineering problems requiring intensive numerical calculations.